Consensus for a power wheelchair training approach for people with cognitive impairments. (2nd January 2023) - Pellichero, Alice; Routhier, François; Sorita, Éric; Archambault, Philippe S.; Demers, Louise; Best, Krista L.
Abstract: Purpose: Power wheelchairs (PWCs) can enhance independent mobility. The World Health Organization recommends training PWC users. However, current PWC training approaches do not always meet the needs of PWC users with complex mobility and cognitive impairment. The aim was to co-develop an innovative approach to PWC training for individuals with complex mobility and cognitive impairments. Materials and methods: A two-phase mixed method research, involving PWC users, clinicians and researchers throughout all aspects of the research, was realized. (1) Interviews and focus groups were used. (2) The Delphi method was followed to refine the PWC training approach. Results: Phase 1: Twenty-six stakeholders indicated that PWC training should consider the client as a partner, the learning environment, the proposed activities, interactions with the trainer and intervention format. Phase 2: two hundred and seven participants agreed that the PWC training should be goal directed, should be client-centred and occupation-based, should enhance client–therapist relationships and should be realized in a safe and adapted environment. Conclusions: Stakeholders on PWC use came to agreement on key components that should be applied when training people with cognitive impairments. Implications for rehabilitation: Stakeholders on power wheelchair (PWC) use came to agreement on key components that should be applied when training people with cognitive impairments. Power wheelchair training should be goal directed, should be client-centred and occupation-based, should enhance client–therapist relationships and should be realized in a safe and adapted environment. Results of this study may contribute to best practices for PWC training and may empower occupational therapists providing PWC in their clinical decision-making.